The importance of effective online teaching training to facilitate the learning process of the foreign languages - Cedillos Bonilla, Fátima Tatiana; Hernández Arévalo, René Guillermo; Serrano Calles, Erly Damary (2024)
It was well known that during the last decade, online learning has gained much more popularity at the educational level because it has great benefits in different levels even though it was not until the pandemic affected the University of El Salvador that the members of the major authorities decided to opt for online teaching method for all the students. This report aims to evaluate how a strong education in online teaching methods can affect the learning process of students from the University of El Salvador. The college has been facing different issues to carry out the learning process via online, particularly during the lockdown period of the coronavirus pandemic in El Salvador. To test the importance of good online teaching training to facilitate the learning process of the foreign languages, diverse e-learning platforms were studied in order to know the different ways to carry out the teaching process. The achievement showed that even if there are many platforms to provide a class, educators need to know how to use well at least five different platforms to supply the needs from the students. The report suggests that even if taking classes online can be as exasperating for the student as for the instructor, particularly for those taking an online course for the first time, the command of the online teaching should be crucial for smooth teaching-learning experience through virtual learning.